2021
DOI: 10.3390/molecules26195914
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Therapeutic Potential of Myristicin: A Literature Review

Abstract: Natural products have been used by humanity for many centuries to treat various illnesses and with the advancement of technology, it became possible to isolate the substances responsible for the beneficial effects of these products, as well as to understand their mechanisms. In this context, myristicin, a substance of natural origin, has shown several promising activities in a large number of in vitro and in vivo studies carried out. This molecule is found in plants such as nutmeg, parsley, carrots, peppers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 67 publications
2
27
0
2
Order By: Relevance
“…The effect of PBFEO fruit essence on reducing the proliferation of colon cancer cells remains a controversial topic despite the ability of the PBFEO plant to inhibit cancer cells (11,12). Accordingly, the current study used MTT assay, flow cytometry, and RT-PCR methods to investigate the cytotoxic effects of the PBFEO fruit essence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of PBFEO fruit essence on reducing the proliferation of colon cancer cells remains a controversial topic despite the ability of the PBFEO plant to inhibit cancer cells (11,12). Accordingly, the current study used MTT assay, flow cytometry, and RT-PCR methods to investigate the cytotoxic effects of the PBFEO fruit essence.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition analysis of the P. bashagardiana fruit essential oil (PBFEO) by Chehrazimeydan et al revealed the presence of myristicin (73.7%) as the major component (10). This finding characterized fruit oil as a rich natural source of myristicin as a phenylpropanoid in-volved in several cellular processes such as cytotoxic activities (11,12). There are limited studies on the cytotoxic effects of the P. bashagardiana fruit essence in colon cancer cell lines, and the standard treatment of colon cancer is surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Myristicin can be used to treat various diseases, for example, diarrhea, stomach aches and anxiety, Crohn’s disease, rheumatoid arthritis, and encephalomyelitis [ 31 ]. Besides, myristicin reveals hepatoprotective [ 32 ], antioxidant [ 33 ], anti-cholinergic [ 34 ], antibacterial [ 35 ], and especially anti-inflammatory properties via numerous biological pathways [ 36 ]. Based on myristicin’s biological benefits, together with its attractive color and fragrance, the plant Eos rich in myristicin content can be exploited for developing aromatherapy and functional supplements.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, anethole has been reported to yield anticancer activity ( Contant, Rouabhia, Loubaki, Chandad, & Semlali, 2021 ). Moreover, myristicin has been described to exert antiproliferative and anti-inflammatory properties ( Seneme, Dos Santos, Silva, Franco, & Longato, 2021 ) and safrole has been reported to promote diverse biological activities, such as antidiabetic, antimicrobial, analgesic, and antifungal activities ( Eid & Hawash, 2021 ).…”
Section: Bioactive Compounds Of Essential Oilsmentioning
confidence: 99%